2005
DOI: 10.1007/s00508-005-0415-y
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella-Enteritidis-Phagentyp-36-Ausbruch in Österreich 2004

Abstract: In June 2004, an egg packing station was epidemiologically incriminated as possibly distributing the vehicle of the Salmonella enterica subsp. enterica ser. Typhimurium definitive type (DT) U291 outbreak which began in September 2003 and--as of June 2004 affected more than 100 persons all over Austria and 8 German tourists. A total of 68 egg producing farms were screened for salmonella. Whereas all samples tested negative for S. Typhimurium DT U291, one batch of laying hens was identified as being heavily cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In this study, the prevalence of NTS isolates from all eggshell swabs was negative. This was also an unexpected result as previous research has shown eggshell contamination to be commonplace [29][30][31][32][33][34][35]. There are several possible explanations for this discrepancy.…”
Section: Discussionmentioning
confidence: 67%
“…In this study, the prevalence of NTS isolates from all eggshell swabs was negative. This was also an unexpected result as previous research has shown eggshell contamination to be commonplace [29][30][31][32][33][34][35]. There are several possible explanations for this discrepancy.…”
Section: Discussionmentioning
confidence: 67%
“…Nevertheless, outbreaks caused by contaminated foodstuffs that are distributed throughout Austria often result in a number of seemingly sporadic single cases where no epidemiologic link has been established. As a result of an outbreak investigation in 2004, 36 microbiologically confirmed S. Enteritidis PT36 cases which involved four provinces could be linked to one contaminated laying hen facility [26]. The flock was culled and the facility was sanitized.…”
Section: Discussionmentioning
confidence: 99%
“…The low prevalence (12.5%) may reflect a reduction of contamination of eggs on poultry farms in Trinidad and Tobago, this hypothesis must be confirmed with further work because the present prevalence study provided information on the contamination of eggs at only a single time point. Salmonellosis associated with contaminated eggs and egg products has been reported in the Caribbean region (8,21) and elsewhere (11,19,26,30,32). However, sample size, isolation techniques used, and time frame should be considered when comparing prevalence data from various studies.…”
Section: Trinidad and Tobago Grenada St Lucia ----------------------mentioning
confidence: 98%
“…Salmonellosis resulting from the consumption of eggs or egg products has been reported in outbreaks globally, with both public health and economic implications (11,19,26,30,32). Rearing of layer birds in Salmonella-free farm environments and obtaining hatching eggs and day-old chicks free of Salmonella have been reported as imperative for preventing Salmonella from entering the human food chain (27,31,35).…”
mentioning
confidence: 99%